1967
DOI: 10.1128/jb.93.2.627-635.1967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Azasteroids on Gram-Positive Bacteria

Abstract: A group of nitrogen-containing steroids closely related in structure was screened for antibacterial activity, by use of Bacillus subtilis and Sarcina lutea as the test organisms. The most active compounds were cholesterol derivatives containing a tertiary or quaternary nitrogen in, or attached to, the A ring. Similar methyltestosterone or progesterone derivatives were inactive. All of the cholesterol derivatives that inhibited growth were surfactant, and, structurally, they would be classified as cationic dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1971
1971
1981
1981

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Previous reports have shown that only the growth of gram-positive organisms was inhibited by gonadal steroids (1,26,27) or by related azasteroids (18,21). No inhibitory effects were detected with a variety of gram-negative organisms.…”
mentioning
confidence: 81%
“…Previous reports have shown that only the growth of gram-positive organisms was inhibited by gonadal steroids (1,26,27) or by related azasteroids (18,21). No inhibitory effects were detected with a variety of gram-negative organisms.…”
mentioning
confidence: 81%
“…Cholesterol and progesterone bind to different sites on the gonococcal membrane. In eucaryotic systems, progesterone binds to either protein (1) or phospholipids (18,19). Miller and Morse (8) showed that progesterone bound readily to isolated gonococcal membrane proteins, although a protein receptor on the intact membrane could not be conclusively demonstrated.…”
Section: Infect Immunmentioning
confidence: 99%
“…Many substances that are inactive in dc polarography give characteristic ac oscillopolarograms. The technique supplements classical polarography but has its own established theory and instrumentation (3)(4)(5)(6).…”
Section: Keyphrases Oscillopolarography-mercaptopurinementioning
confidence: 99%